Adaptación de cuatro variedades de ajo (Allium sativum l.) con tres niveles de abono orgánico en el cantón La Maná 2013 - Pallo Toaquiza, Juan Elias (2014)
In Ecuador, as in other countries of the world, the problems caused by pollution from the use of fertilizers which are produced by chemical industries which have been finishing off the fertility of the soil and also affect the healthof farmers, for this reason the need of the research in the short-cycle crops, such as: the garlic is set out.